Study on heat extraction characteristics in a rock fracture for the application of enhanced geothermal systems. (December 2022) - Zhang, Le; He, Jiayuan; Wang, Haibo; Cen, Xueqi
Highlights: A numerical model of high pressure water flowing through a rough rock was established. A compensating method was proposed for optimize flow rate to postpone thermal breakthrough. The influence of thermo-physical properties on heat extraction performance were clarified. Abstract: Enhanced geothermal systems (EGS) technologies aim to extract geothermal energy from hot dry rock (HDR). Heat extraction performance is of great importance for thermal efficiency and life cycle of EGS. It is intuitively considered that EGS reservoir modeling should be established based on accurate measured data of thermal and hydraulic properties of rock matrix and fluid, such as thermal conductivity, heat capacity and fracture permeability, however, which are time-consuming to obtain in some projects. This paper aims to clarify the influence of these parameters on heat extraction performance, which can provide basis for reservoir model simplification during preparation process of engineering scheme. Numerical simulations were carried out based on a rough fracture of granite rock at core scale, which has been validated by amount of experiments. First, the differences between simulation results and the previous experiment results were presented and analyzed, for variations of heat extraction rate per flow rate. Compared with the method with constant flow rate, the compensating method with various flow rate greatly increased the heat extraction rate and postpone thermal breakthrough time. Therefore, a simplified method was proposed in this paper to optimize the flow rate or predict the heat extraction rate when EGS operation with various flow rates. The method are applicable for geothermal reservoir management for efficient and stable heat extraction. Finally, the effects of properties of rock mass and fracture were studied. The production temperature and heat extraction rate were larger with larger thermal conductivity and heat capacity. It was found that the maximum influence on heat extraction rate were less than 20% and 10% within the common value ranges of thermal conductivity and heat capacity, respectively. There were almost no differences in the heat transfer process in fractures with different fracture permeabilities. It can be concluded that the prediction error of heat extraction performance is tolerable for engineering reservoir simulations, even without precise experimental test for thermal and hydraulic properties variations with temperature or pressure.